Enhancing Teacher Competence in the Digital Era: Strategies for Professional Development and Resilience - Rangkuti, Zulkifli (Ilomata International Journal of Social Science, 2025)
In the rapidly evolving digital era, enhancing teacher competence has become a critical focus for educational institutions globally. The integration of technology into teaching and learning processes necessitates continuous professional development and resilience among educators. This study, employing a qualitative literature review method, explores various strategies to enhance teacher competence in the digital age. It identifies key approaches including digital literacy training, collaborative learning communities, mentorship programs, and self-directed learning to improve teachers' technological skills and pedagogical practices. Additionally, the study examines how fostering resilience can help educators adapt to the challenges and pressures associated with technology integration. The findings emphasize the importance of professional development frameworks that not only focus on technological skills but also emphasize psychological well-being and adaptability. By identifying successful strategies, this paper provides valuable insights for policymakers, educational leaders, and teachers to improve the overall quality of education in the digital era.